Proceedings of the 56th Annual Meeting of the Association for Computational Linguistics (Volume 1: Long Papers) 2018
DOI: 10.18653/v1/p18-1002
|View full text |Cite
|
Sign up to set email alerts
|

A La Carte Embedding: Cheap but Effective Induction of Semantic Feature Vectors

Abstract: Motivations like domain adaptation, transfer learning, and feature learning have fueled interest in inducing embeddings for rare or unseen words, n-grams, synsets, and other textual features. This paper introducesà la carte embedding, a simple and general alternative to the usual word2vec-based approaches for building such representations that is based upon recent theoretical results for GloVe-like embeddings. Our method relies mainly on a linear transformation that is efficiently learnable using pretrained wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
110
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(123 citation statements)
references
References 32 publications
2
110
0
Order By: Relevance
“…where c = C∈C |C ∩ V| is the total number of words in C for which embeddings exist. In accordance with results reported by Khodak et al (2018), we found it helpful to apply a linear transformation to the so-obtained embedding, resulting in the final context embeddinĝ…”
Section: The Form-context Modelsupporting
confidence: 89%
See 3 more Smart Citations
“…where c = C∈C |C ∩ V| is the total number of words in C for which embeddings exist. In accordance with results reported by Khodak et al (2018), we found it helpful to apply a linear transformation to the so-obtained embedding, resulting in the final context embeddinĝ…”
Section: The Form-context Modelsupporting
confidence: 89%
“…Our approach is able to generate embeddings for OOV words even from only a single observation with high accuracy in many cases and outperforms previous work on the Definitional Nonce dataset (Herbelot and Baroni 2017) and the Contextual Rare Words dataset (Khodak et al 2018). To the best of our knowledge, this is the first work that jointly uses surface-form and context information to obtain representations for novel words.…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…However, the method comes with a potential limitation: for each latent feature taking form as a PC of the word vectors, ABTT either completely removes the feature or keeps it intact. For this reason, Khodak et al (2018) argued that ABTT is liable either to not remove enough noise or to cause too much information loss. The objective of this paper is to address the limitations of ABTT.…”
Section: Post-processing Word Vectors Via Conceptor Negationmentioning
confidence: 99%